The Influence of Motivation, Entrepreneurial Commitment, and Business Networks on the Sustainability of MSMEs - Prasetyo, Vinsensius Widdy Tri; Cahyadi, Andi (JMK (Jurnal Manajemen dan Kewirausahaan), 2024)
Business continuity as an important concept in determining the decision to continue business operations. The key to business sustainability includes economic and non-economic benefits for individuals, the economy and society. To survive, the pecel chili industry in Madiun City must have motivation, commitment, and business networks in running a business. The purpose of this article is to examine the important role of motivation, entrepreneurial commitment, and business networks and their influence on business sustainability, a study on Sambal Pecel MSMEs in Madiun City. This study uses a quantitative method to prove the influence of the variables studied. The unit of analysis for this study was the Sambal Pecel in the Madiun City area with a total of 57 Sambal Pecel respondents. Entrepreneurial motivation, entrepreneurial commitment, and business networks have an important role in the sustainability of Sambal Pecel in Madiun City. This is as evidenced by the results of multiple linear regression analysis which has proven the results of the significant influence of entrepreneurial motivation, entrepreneurial commitment, and business networks on the sustainability of the Sambal Pecel in Madiun City.